A note on the chronic effects of tall oil on the variegetd cutworm, Peridroma saucia [Lepidoptera : Noctuidae] - Xie, Y.S.; Isman, M.B. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1992)
Chronic effects of tall oil, a by-product of the kraft pulping process of softwoods, on the variegated cutworm, Peridroma saucia, were assessed via incorporation into artificial diet. At a dietary concentration of 1.5% fresh weight, depitched tall oil (DTO) significantly reduced P. saucia weight, prolonged developmental time, and increased mortality in different stages. A significant linear relationship was found between dietary concentration of DTO and ail developmental parameters tested. A diet-shift experiment clearly demonstrated that the inhibitory effect of DTO to P. saucia is persistent and not readily alleviated by transferring larvae to untreated diet. DTO may be a useful natural agent for pest management.